Expressive B-spline curves: a pilot study on a flexible shape representation - Seah, Hock Soon (2024)
We present a pilot study on eXpressive B-SplineCurves (XBSC), an extension of Disk B-Spline Curves (DBSC). XBSC facilitates expressive drawings in terms of shape and color. For shape, colors on both sides of XBSC strokes are defined independently instead of using a single parameter for both sides as in DBSC. We perform coloring by considering the envelopes of XBSC as diffusion curves. Our results show that XBSC can be used to easily draw a wide range of images with fewer number of primitives compared to previous methods.